Pengaruh Corona Virus Disease terhadap Penjualan Produk Suplemen Kesehatan - Khotimatul Khusna; Rita Septiana; Ghani Nurfiana Fadma Sari; Isma Rosida (Jurnal Farmasi Indonesia, 2021)
Corona Virus Disease-19 (COVID-19) has been declared a pandemic by the World Health Organization (WHO) on March 11, 2020, previously on March 2, 2020 Indonesia has reported 2 confirmed cases of COVID-19. Immunomodulators that can increase the body's resistance to the COVID-19 virus by stimulating the immune system. The purpose of this study was to determine the effect of COVID-19 on the sale of health supplement products in a pharmacy in Surakarta.This research is an analytical observational research. Data was collected from sales records at pharmacies in the 3 months before the COVID-19 pandemic and 3 months at the beginning of the COVID-19 pandemic. Data analysis using statistical tests.Sales of health supplement products for 6 months were 17843 pcs. There were 4773 health supplement products sold before the pandemic, while 13070 pcs were sold during the pandemic. The results of the normality test showed that the data were not normally distributed. The Wilcoxon test results show that the significant value is 0.028 (<0.05), meaning that there is a difference in sales before and after the determination of the pandemic. The conclusion of this study is that COVID-19 has an effect on the sale of health supplement products in a pharmacy in Surakarta.